Matrices Satisfying Regular Minimality - Trendtel, Matthias; Ünlü, Ali; Dzhafarov, Ehtibar (Frontiers in Psychology, 2010)
A matrix of discrimination measures (discrimination probabilities, numerical estimates of dissimilarity, etc.) satisfies Regular Minimality (RM) if every row and every column of the matrix contains a single minimal entry, and an entry minimal in its row is minimal in its column. We derive a formula for the proportion of RM-compliant matrices among all square matrices of a given size and with no tied entries. Under a certain “meta- probabilistic” model this proportion can be interpreted as the probability with which a randomly chosen matrix turns out to be RM-compliant.